A Cumulative Risk and Resilience Model of Dyslexia - Catts, Hugh W.; Petscher, Yaacov (Journal of learning disabilities, 2022)
Considerable attention and legislation are currently focused on developmental dyslexia. A major challenge to these efforts is how to define and operationalize dyslexia. In this article, we argue that rather than defining dyslexia on the basis of an underlying condition, dyslexia is best viewed as a label for an unexpected reading disability. This view fits well with a preventive approach in which risk for reading disability is identified and addressed prior to children experiencing reading failure. A risk–resilience model is introduced that proposes that dyslexia is due to the cumulative effects of risk and resilience factors. Evidence for the multifactorial causal basis of dyslexia is reviewed and potential factors that may offset this risk are considered. The implications of a cumulative risk and resilience model for early identification and intervention is discussed.